The Surroundings Medicinal Plants and its Utilization for Women Healthcare in Masbangun Village, Kayong Utara District - Fathul Yusro; Rania Rania; Yeni Mariani; Evy Wardenaar; Yanieta Arbiastutie (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2020)
The knowledge of medicinal plants possessed by traditional healers (battra) must be transmitted to the next generation, one of them by using plants that are around to overcome health problems related to feminity. This study aims to analyze the level of community knowledge on the plant species that are used to overcome some issues related to femininity, the plants most widely used by the community, and the plant species most preferred for the treatment of certain diseases to femininity. The research method was conducted by interview technique with purposive sampling. The respondents' number is 30% of the total households in the village of Masbangun (320 respondents). The interviews were conducted using a questionnaire containing several questions related to the surrounding plant species used by the community to address health problems related to femininity. The results showed that most people in Masbangun Village (90%) knew the benefits of medicinal plants in the surrounding environment. A total of 16 types of medicinal plants are used as ingredients for women's health care. The plants that have a high use value are the heart of a Musa paradisiaca, Zingiber officinale, Curcuma domestica, and Piper betle. Medicinal plants with the highest FL values are Zingiber purpureum, Centella asiatica, Zingiber officinale (pre/postpartum), Musa paradisiaca (breastfeeding), Quercus infectoria (vaginal discharge), Premna cordifolia (body odor), Vigna radiata (female fertility) and Cocos nucifera (blackening hair). The level of utilization of medicinal plants by the community in Masbangun Village is in the medium category (6-10 species). The majority of users are women between the ages of 41-60 and 21-40 years old, elementary school education, work of housewives, and farmers.